2020
DOI: 10.1111/cea.13761
|View full text |Cite
|
Sign up to set email alerts
|

Possible association between early formula and reduced risk of cow’s milk allergy: The Japan Environment and Children’s Study

Abstract: Environment, Children's Study (JECS) Group This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 20 publications
3
23
0
Order By: Relevance
“…While for high-risk infants suffering from severe eczema and atopic dermatitis, a delayed introduction constitutes a considerable risk of developing an allergy in the future, and no credible data are available for medium-risk and low-risk children [6,47]. Furthermore, current investigations have shown that only peanut and egg allergens might negate the onset of allergic complications in Asian populations, and no findings have been reported considering other foods [48,49]. Therefore, with respect to the low prevalence of egg and peanut allergies in these ethnicities, supplementary examinations are required to establish a credible connection between the benefits of early and late introduction of food allergens.…”
Section: Insights From Asian-focused Researchmentioning
confidence: 97%
“…While for high-risk infants suffering from severe eczema and atopic dermatitis, a delayed introduction constitutes a considerable risk of developing an allergy in the future, and no credible data are available for medium-risk and low-risk children [6,47]. Furthermore, current investigations have shown that only peanut and egg allergens might negate the onset of allergic complications in Asian populations, and no findings have been reported considering other foods [48,49]. Therefore, with respect to the low prevalence of egg and peanut allergies in these ethnicities, supplementary examinations are required to establish a credible connection between the benefits of early and late introduction of food allergens.…”
Section: Insights From Asian-focused Researchmentioning
confidence: 97%
“…37 It may be that early exposure alone is insufficient and that both early and prolonged exposure is necessary to decrease the risk of allergy. 38 In our study, cow's milk IgG4 levels were significantly higher at 3 months in the control group compared with the intervention group, suggesting that early oral exposure to cow's milk induces IgG4 class switching. In addition to the primary prevention of peanut allergy, 35 raised IgG4 levels have also been associated with successful immunotherapy for cow's milk protein allergy.…”
Section: Asthmamentioning
confidence: 42%
“…Epidemiologically, breast feeding may provide a reduced risk of child allergic diseases [34], whereas formula milk feeding may result in an increased risk [35]. However, the JECS data suggested an association between early formula milk intake and a reduced risk of cow's milk allergy [36]. Additionally, drinking cow's milk might be associated with a higher risk of developing allergies [37,38].…”
Section: Discussionmentioning
confidence: 99%